2020
DOI: 10.1038/s41467-020-19186-x
|View full text |Cite
|
Sign up to set email alerts
|

Natural antisense transcripts of MIR398 genes suppress microR398 processing and attenuate plant thermotolerance

Abstract: MicroRNAs (miRNAs) and natural antisense transcripts (NATs) control many biological processes and have been broadly applied for genetic manipulation of eukaryotic gene expression. Still unclear, however, are whether and how NATs regulate miRNA production. Here, we report that the cis-NATs of MIR398 genes repress the processing of their pri-miRNAs. Through genome-wide analysis of RNA sequencing data, we identify cis-NATs of MIRNA genes in Arabidopsis and Brassica. In Arabidopsis, MIR398b and MIR398c are coexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 81 publications
2
53
1
Order By: Relevance
“…In particular, lncNATs are correlated with the response to various abiotic and biotic stresses [29,34,37]. For example, a recent study in Arabidopsis revealed that NATs affect plant thermotolerance [38].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, lncNATs are correlated with the response to various abiotic and biotic stresses [29,34,37]. For example, a recent study in Arabidopsis revealed that NATs affect plant thermotolerance [38].…”
Section: Introductionmentioning
confidence: 99%
“…As a primary catalyst of oxygen free radicals, superoxide dismutase plays an important role in the stress tolerance of rice. Many studies have revealed that increased expression of SOD improves stress tolerance in plants (Liu et (Li et al 2020), however the protein level expression of SODs are not reported in rice. In our study, a rabbit polyclonal antibody against OsCu/Zn SOD was used to test its expression under high-temperature.…”
Section: Discussionmentioning
confidence: 99%
“…MiR398 exhibits strong homology betreen Arabidopsis thaliana and rice. Many studies have shown that Cu/Zn SOD in rice is also regulated by miR398 (Balyan et al 2017; Yao et al 2014; Li et al 2019) and there are muti-level regulation among Natural antisense transcripts of MIR398, miRNA and SOD in Arabidopsis thaliana (Li et al 2020), however the protein level expression of SODs are not reported in rice. In our study, a rabbit polyclonal antibody against OsCu/Zn SOD was used to test its expression under high-temperature.…”
Section: Rabbit Anti-oscu/zn Sod Is Cross Reactive With Sod From Tomamentioning
confidence: 99%
“…Knock-down of NAT398b/c promotes the accumulation of MIR398b and MIR398c, while the overexpression of NAT398b and NAT398c represses the processing of miR398. Notably, the overexpression of siRNAs derived from NAT398 overlapping transcripts, so-called nat-siR398, reduces the levels of pri-miR398b and pri-miR398c [37].…”
Section: Lncrnas As Precursors Of Small Regulatory Rnasmentioning
confidence: 99%